Physics graduate preparedness: A human capabilities perspective - Audu, Bako Nyikun; Conana, Christiana; Marshall, Delia (Critical Studies in Teaching and Learning, 2025)
In South Africa and globally, the preparedness of physics graduates for the workplace and societal challenges is increasingly prioritised. This study, framed by a human capabilities approach, explores physics students’ and graduates’ perceptions of the development of their graduate preparedness. Findings revealed various interconnected conversion factors that are seen to differently enable or hinder students’ ability to transform educational resources and opportunities into desired capabilities and functionings. These included personal factors such as motivation and computational skills; social factors such as teaching approach, opportunities for peer engagement inside and outside the classroom, and career guidance; and environmental factors related to the urban setting of the university. The study highlights implications for teaching and institutional arrangements, including more explicit focus on fostering desired graduate attributes, developing student voice, and enhancing career exposure. The study explores how universities could better equip physics graduates as critical citizens to advance individual and societal well-being.